2013
DOI: 10.1089/ast.2013.0993
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of the Ice-Albedo Feedback on Atmospheric Properties

Abstract: Ice-albedo feedback is a potentially important destabilizing effect for the climate of terrestrial planets. It is based on the positive feedback between decreasing surface temperatures, an increase of snow and ice cover, and an associated increase in planetary albedo, which then further decreases surface temperature. A recent study shows that for M stars, the strength of the ice-albedo feedback is reduced due to the strong spectral dependence of stellar radiation and snow/ice albedos; that is, M stars primaril… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
1
29
0
1
Order By: Relevance
“…Low mass stars have a redder spectrum and this changes the albedo of the ice and snow (Joshi & Haberle 2012;von Paris et al 2013). Taking this phenomenon into account would radically change the ice-albedo feedback, so that for redder objects it would not be able to drive the planets into a glaciation state (as we showed here for planets with high eccentricities around a L = 10 −2 L star).…”
Section: Discussionmentioning
confidence: 78%
“…Low mass stars have a redder spectrum and this changes the albedo of the ice and snow (Joshi & Haberle 2012;von Paris et al 2013). Taking this phenomenon into account would radically change the ice-albedo feedback, so that for redder objects it would not be able to drive the planets into a glaciation state (as we showed here for planets with high eccentricities around a L = 10 −2 L star).…”
Section: Discussionmentioning
confidence: 78%
“…This would lead to low water vapor saturation pressures, regardless of which relative humidity profile is assumed (see below). Furthermore, for the variation in surface albedo we expect a smaller impact as for the scenarios discussed here, since, to reach habitable surface temperatures at the outer edge of the habitable zone, high amounts of CO 2 are required that mask the surface albedo, as shown by Shields et al (2013) and von Paris et al (2013). As expected, the largest orbital distances for habitable surface conditions are found for the Earthlike planet when assuming the lowest surface albedo of 0.07 and a high relative humidity (fully saturated atmosphere, corresponding to the highest amount of greenhouse gases in the considered scenarios).…”
Section: Resultsmentioning
confidence: 89%
“…The warming caused by atmospheric CO 2 and water vapor absorbing strongly in the near-IR, where M dwarfs emit strongly, has been established for some time, based on earlier work (Kasting et al, 1993;Selsis et al, 2007). And recent studies have continued to explore the effect of stellar SED on the vertical temperature structure of an orbiting planet's atmosphere, and its resulting climate (Shields et al, 2013;von Paris et al, 2013;Godolt et al, 2015). What has only recently emerged is an understanding of the influence on climate of the interaction between the SED of an M-dwarf host star and the icy and snowy surfaces of an orbiting planet.…”
Section: Radiative Effectsmentioning
confidence: 99%
“…As a result, the ice-Albedo feedback mechanism, which is largely cooling on the Earth, may be suppressed on M-dwarf planets (Joshi & Haberle, 2012). Comprehensive follow-up studies of this phenomenon carried out with a hierarchy of radiative transfer and climate models found that lower-mass planets exhibit warmer climates than planets orbiting hotter, more luminous stars at equivalent stellar flux distances (Shields et al, 2013;von Paris et al, 2013). M-dwarf planets appear less susceptible to snowball states, requiring a larger decrease in instellation for global glaciation (Shields et al, 2013).…”
Section: Radiative Effectsmentioning
confidence: 99%
See 1 more Smart Citation